Design of a Phase 1/2 study of an AAV9‐based gene therapy for fronto‐temporal dementia patients with pathogenic GRN mutations (PROCLAIM trial): Human/Trial design. (7th December 2020) - Uspenskaya‐Cadoz, Olga; Benoit, Jamie; Mahoney, Erin; Velaga, Jenny; Sondergaard, Patricia; Lowrey, Mark; Sevigny, Jeffrey
Abstract: Background: The GRN gene encodes progranulin (PGRN), a secreted glycoprotein broadly expressed in the CNS and periphery in a variety of cells. PGRN is implicated in several physiological functions including as an activator of lysosome function, an anti‐inflammatory factor, a neurotrophic factor, and a growth factor. Patients suffering from fronto‐temporal dementia with GRN mutations (FTD‐GRN) carry a single mutation in the GRN gene, resulting in haploinsufficiency and an approximately 50% reduction in PGRN levels. GRN mutation carriers have an approximately 90% risk of developing FTD by age 75. FTD‐GRN is a rapidly progressing dementia with no approved treatment options. In FTD‐GRN patients, the delivery of a functional copy of the GRN gene by a recombinant adeno‐associated virus serotype 9 (rAAV9) directly to the CNS may normalize PGRN levels, potentially restoring lysosomal function and slowing neurodegeneration, thus resulting in modification of disease progression. Methods: PROCLAIM is a Phase 1/2 randomized, open‐label, ascending dose study to evaluate the safety and efficacy of PR006 in patients with FTD‐GRN. The study will evaluate three dose levels of PR006 in ascending dose cohorts. A total of 15 patients with symptomatic‐stage FTD ascertained by the CDR plus NACC FTLD sub of boxes score will receive PR006 at a low, mid or high dose, administered sub‐occipitally intra cisterna magna. The primary objective is to evaluate safety and tolerability of PR006, as well as to quantify the change in PGRN levels in blood and CSF. Secondary objectives are to assess pharmacodynamic effects of PR006 on neurofilament light chain protein, clinical decline assessed by the CDR plus NACC FTLD instrument, and immunogenicity. Exploratory objectives include the assessment of clinical symptom burden, MRI measures of cortical atrophy and white matter hyperintensities, and biomarkers of neuroinflammation and astroglial pathology. Result: The PROCLAIM trial is planned to open patient enrollment in 2020. Conclusion: PROCLAIM will assess dose, safety, tolerability, biomarker and efficacy effects of PR006 and inform its further clinical development.